Infiltrated silver-based electric contact material and preparation method thereof
The AgMe(semi)/Ag composite skeleton structure is constructed through an integrated molding process, which solves the problems of instability in density and low material yield caused by misalignment of seepage in the prior art, and achieves higher material density and longer electrical contact life.
Patent Information
- Application Number
- CN202411643791.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
During mass production, existing melted silver-based electrical contact materials have problems such as misalignment of seepage sheets, holes inside electrical contacts, and reverse silver seepage on the silver point surface, resulting in unstable density, low material yield, poor temperature rise, and poor arc corrosion resistance.
The AgMe(semi)/Ag composite skeleton structure is constructed by an integrated molding process, and the AgMe(final) electrical contact composite material is formed through mixing and grinding, glue mixing and granulation, double-layer pressing molding, degumming and high-temperature seepage.
It effectively avoids the density inconsistency caused by misalignment of seepage, improves the density and material yield of the material, extends the service life of the electrical contacts, reduces temperature rise, and reduces production costs.
Smart Images

Figure CN119501052A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electric contact materials, and in particular to a melt-infiltration silver-based electric contact material and a preparation method thereof. Background Art
[0002] AgMe series electrical contact materials are widely used in medium and low voltage circuit breakers, universal switches, and electrode products in the field of power electronics because of their good electrical conductivity, thermal conductivity, resistance to fusion welding, and resistance to arc erosion. The reinforcing phase Me is tungsten W, tungsten carbide WC, tungsten-graphene-nickel or any other material that can be used to make a melt infiltration skeleton.
[0003] When the silver content of AgMe electrical contact materials is less than 70%, they are mostly prepared by melt infiltration. As we all know, the conventional AgMe material melt infiltration process requires the preparation of a skeleton structure first, and then placing Ag infiltration sheets or AgCu infiltration sheets in a graphite tray for melt infiltration. This process requires two times of placing the material on the tray. During mass production, the skeleton and infiltration sheets in the tray are prone to misalignment, which in turn affects the flow of silver during subsequent melt infiltration, and easily leads to the situation where no infiltration sheet material infiltrates the local area of the skeleton, which in turn leads to a low yield of AgMe materials, holes in the organization, and poor density. During the working process of the AgMe electrical contact, under the heat and force of the arc, cracks rapidly expand from these holes, accelerating the burning of the material, which reduces the arc erosion resistance of the AgMe electrical contact and shortens its life. In addition, when the infiltration sheet is misplaced or the melt infiltration is improper, it is also easy to cause the silver liquid phase to reversely infiltrate from the skeleton, resulting in silver accumulation and pitting on the surface of the electrical contact, and unstable contact resistance on the surface of the electrical contact, which seriously affects the temperature rise of the AgMe electrical products.
[0004] After searching the existing technologies of preparation methods of melt-infiltration electrical contact materials at home and abroad, it was found that patent CN116618656A sprays a layer of carbon powder, inorganic non-metallic oxide and organic solution on the surface of the electrical contact to make the surface of the electrical contact free of silver layer, which is not easy to form silver pile, pitting, silver layer fracture, uneven thickness of the surface silver layer and other abnormalities, and can well improve the corrosion resistance of the contact. However, this method still adopts the method of silver infiltration in a plate, and the uneven silver infiltration inside AgMe is not effectively improved, and the material density is not improved. In addition, the process is relatively complicated and the production cost is high.
[0005] Patent CN108441668A uses a melt infiltration process with external air pressure to obtain an AgWNiC material, which improves the bonding strength between the skeleton and silver, but cannot completely avoid the internal holes and surface silver infiltration of the electrical contacts, nor can it avoid the problem of misalignment of the skeleton and the infiltrated sheet in the material tray.
[0006] Most of the other patents improve the wettability of the skeleton and silver, reduce the pores inside the product, and increase the density of the material. However, they all adopt the method of plate infiltration. In the subsequent mass production, there is still the problem of misalignment of the infiltration sheets, which leads to pore defects inside some products and low yield rate. Summary of the invention
[0007] In view of the defects in the prior art, the purpose of the present invention is to provide a melt-infiltration type silver-based electrical contact material and a preparation method thereof, which can replace the existing melt-infiltration process to solve the problems of batch production of melt-infiltration type electrical contact materials, such as misalignment of infiltration sheets, internal holes in electrical contacts, reverse silver infiltration on the surface of silver points, pitting, etc., which lead to at least one of the problems of unstable density of batch products, low yield, poor temperature rise, and low arc erosion resistance.
[0008] According to one aspect of the present invention, a method for preparing a melt-infiltrated silver-based electrical contact material is provided, comprising:
[0009] Mixing and grinding Ag powder, reinforcing phase Me powder and additive powder to obtain AgMe composite powder containing additive;
[0010] The AgMe composite powder containing additives is mixed with glue and granulated;
[0011] The granulated AgMe composite powder is double-layer pressed, where the lower layer is AgMe (半) layer, the upper structure is Ag layer, and AgMe (半) / Ag composite body;
[0012] The AgMe (半) The Ag / Ag composite body is debonded to obtain AgMe (半) / Ag composite framework;
[0013] The AgMe (半) / Ag composite framework is melt-infiltrated at high temperature to obtain AgMe (终) The electric contact composite material is a melt-infiltration type silver-based electric contact material.
[0014] Optionally, the Ag powder, the reinforcing phase Me powder and the additive powder are mixed and ground, wherein:
[0015] The content of the reinforcing phase Me powder is not less than 35wt% and not more than 85wt% of the total weight of the finished product after infiltration, the content of the additive powder is not more than 3wt% of the total weight of the mixed powder, and the balance is Ag powder;
[0016] The additive powder is an element or compound that can be wetted with the reinforcing phase Me powder and cannot be infinitely mutually soluble with Ag;
[0017] The particle size of the Ag powder is 100nm-50μm; the particle size of the reinforcing phase Me powder is 50nm-20μm.
[0018] Optionally, the Ag powder, the reinforcing phase Me powder and the additive powder are mixed and ground, wherein:
[0019] The mixing and grinding is carried out by any one of dry mixing and grinding, wet mixing and grinding, and dry mixing and grinding followed by wet mixing. The mixing and grinding time is 0.5 to 24 hours; and the ball-to-material ratio is 1 to 10.
[0020] Optionally, the AgMe composite powder containing additives is subjected to rubber mixing and granulation. The rubber mixing and granulation comprises:
[0021] Adding a molding agent to the AgMe composite powder, granulating, and then drying; wherein the molding agent used is a mixed solution of one or more of PVA, PEG and PVP, and the weight percentage of the molding agent used in the AgMe composite powder containing the additive is 0.2wt% to 20wt%;
[0022] The mixing temperature of the glue is 70-100°C, the drying temperature is 75-110°C, and after drying, it is sieved with a mesh number of 40-400 meshes.
[0023] Optionally, the granulated and dried AgMe (半) The powder is pressed into shape, including:
[0024] First, the AgMe composite powder after granulation and drying is placed in the molding machine mold for the first pre-pressing to obtain AgMe (半) Semi-finished green products;
[0025] Then in the mold cavity, AgMe (半) Ag powder is added to the upper part of the semi-finished green body, and the second pressing is performed to obtain the lower layer of AgMe (半) , AgMe with Ag powder on the upper layer (半) / Ag composite body.
[0026] Optionally, in the first pre-pressing, the weight G1 of the AgMe composite powder after granulation and drying is calculated as follows: G1 = [L 1 *L 2 *H*ρ*(1-C 2 )] / (1-C 1 -C 3 );
[0027] In the formula, C 1 is the silver content of AgMe composite powder, C 3 C is the glue content of AgMe composite powder; 2 For AgMe (终)Silver content in finished electrical contact composite materials, ρ is AgMe (终) Density of finished electrical contact composite material, L 1 , L 2 , H are AgMe (终) The length, width and thickness of the finished electrical contact composite material;
[0028] The AgMe (半) The size of semi-finished green body and AgMe (终) The finished electrical contact composites have the same dimensions.
[0029] Optionally, in the second pressing, the weight g1 of the added Ag powder is calculated as follows: g1 = (L 1 *L 2 *H*ρ)-G1*(1-C 3 );
[0030] Where, L 1 , L 2 , H are AgMe (终) The length, width and thickness of the finished electrical contact composite material; ρ is AgMe (终) Density of finished electrical contact composite material, G1 is the weight of AgMe composite powder after granulation and drying, C 3 is the glue content of AgMe composite powder;
[0031] The AgMe (半) In the Ag / Ag composite body, the Ag powder layer is used to infiltrate and fill the AgMe (半) Layer skeleton pore material.
[0032] Optionally, the AgMe (半) The Ag / Ag composite body is debonded, wherein: the debonding temperature is 300°C to 650°C, the debonding time is 0.5 hour to 10 hours, and the debonding atmosphere is H 2 , any one of hydrogen and nitrogen mixed gas and vacuum.
[0033] Optionally, the AgMe (半) / Ag composite skeleton is subjected to high temperature infiltration, including: debonding AgMe (半) The / Ag composite framework is placed in a continuous furnace and infiltrated under a protective atmosphere;
[0034] The infiltration temperature is 980℃~1200℃, the infiltration time is 2 hours~7 hours, and the infiltration atmosphere is H 2 Or hydrogen and nitrogen mixed gas.
[0035] According to another aspect of the present invention, there is provided a melt-infiltration type silver-based electrical contact material, which is prepared by using the above-mentioned method for preparing the melt-infiltration type silver-based electrical contact material.
[0036] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0037] 1. The present invention adopts an integrated molding process to construct AgMe (半) Compared with the infiltration method of swinging the plate, the composite skeleton structure of AgMe can avoid the problem of inconsistent density of the infiltration product caused by the misalignment of the infiltration sheet, as well as the movement of the infiltration sheet during the infiltration and pushing process, deviation from the AgMe skeleton, and inability to infiltrate. The method of the present invention can reduce the generation of defective products, improve the material density and yield rate of batch products, and effectively improve the defects such as holes in the product, thereby increasing the arc erosion resistance of the product. In addition, AgMe (半) The silver powder required for the Ag / Ag composite framework is evenly distributed in the AgMe (半) On one side of the skeleton, the reverse penetration of the electrical contacts and uneven surface silver penetration are effectively improved, making the surface contact resistance of the product stable and effectively improving the temperature rise of the electrical products.
[0038] 2. The method of the present invention eliminates the secondary panning and sheeting process and is easy to realize mass production. Since the one-piece molding process does not require the separate production of sheeting, the sheeting processing and production can be omitted, so the method has the characteristics of high efficiency and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0040] Figure 1 The AgW prepared in one embodiment of the present invention (半) Microstructure metallographic image of the composite skeleton of Ag / Ag, with the lower layer being AgW (半) Porous structure, the upper layer is pure Ag structure;
[0041] Figure 2 This is the AgW50 microstructure after infiltration in one embodiment of the present invention, in which the reinforcing phase W is dispersedly distributed and the microstructure is uniform. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0043] A method for preparing a melt-infiltration silver-based electrical contact material provided by an embodiment of the present invention comprises the following steps:
[0044] S1, mixing and grinding Ag powder, reinforcing phase Me powder and additive powder to obtain AgMe composite powder containing additives;
[0045] S2, mixing and granulating the AgMe composite powder containing additives;
[0046] S3, the granulated AgMe composite powder is double-layer pressed, wherein the lower layer structure is AgMe (半) layer, the upper structure is Ag layer, and AgMe (半) / Ag composite body;
[0047] S4. AgMe (半) The Ag / Ag composite body is debonded to obtain AgMe (半) / Ag composite framework;
[0048] S5. AgMe (半) / Ag composite framework is melt-infiltrated at high temperature to obtain AgMe (终) The electric contact composite material is a melt-infiltration type silver-based electric contact material.
[0049] In some embodiments, in step S1, the content of the reinforcing phase Me powder is not less than 35wt% and not more than 85wt% of the overall weight of the finished product after infiltration. For the finished product, if the content of the reinforcing phase Me powder is less than 35% of the overall weight, the blank is prone to form closed pores during the infiltration process and cannot be infiltrated; and if the content of the reinforcing phase Me powder is higher than 85% of the overall weight, the "formability" of the infiltrated blank is too poor and cannot be demolded, or a large number of cracks will appear in the blank after demolding. The above-mentioned content setting of the reinforcing phase Me powder can satisfy the "formability" of the infiltrated blank. The additive powder content is not higher than 3wt% of the total weight of the mixed powder (the powder mixed with Ag powder, reinforcing phase Me powder and additive powder in step S1), and the remainder is Ag powder. If the additive powder content is greater than 3% of the total weight, it will affect the content of the overall reinforcing phase Me powder, thereby causing problems such as poor wear resistance of the product. The additive powder is an element or compound that can be wetted with the reinforcing phase Me powder and cannot be infinitely mutually fused with Ag, such as Ni, Co, ZnO 2The additive powder can improve the wettability of the interface between the reinforcing phase Me powder and silver, thereby improving the infiltration effect and preventing uneven infiltration process; the additive powder can also improve the electrical properties of the product, such as breaking capacity and arc ablation resistance; the Ag powder particle size is 100nm~50μm; the reinforcing phase Me powder is tungsten W, tungsten carbide WC, tungsten carbide graphite WCC, tungsten-graphene-nickel, or any one or more other materials that can be used to make infiltration skeletons, and the reinforcing phase Me powder particle size is 50nm~20μm. The particle size of each powder mainly considers the powder matching during the powder mixing process of the powder metallurgy process, that is, the principle of "close stacking", so that the density is as large as possible under the same volume. In this way, the density of the powder during molding can be improved.
[0050] In step S1, the ball milling method, ball milling time and ball-to-material ratio are mainly determined according to the dispersion and uniformity of the powder. If the mixing time is too short, the powder cannot be mixed evenly; if the mixing time is too long, although the powder is mixed evenly, it affects the production efficiency. If the specific gravity of the ball is too large, the amount of powder added to the same tank is small, which affects the production efficiency; if the specific gravity of the ball is too small, it is impossible to achieve a good collision between the balls, so that the uniformity of powder mixing is affected. In some embodiments, Ag powder, Me powder and additive X powder are placed in a powder mixer, and the mixing is carried out by dry mixing, wet mixing and first dry mixing and then wet mixing. Preferably, dry mixing and then wet mixing are used to improve the uniformity of powder mixing; the mixing time is 0.5 to 24 hours; the ball-to-material ratio (i.e., the weight ratio of balls and powder) is 1 to 10. Thus, AgMe composite powder containing additive X is obtained.
[0051] In step S2, the powder that has not been granulated with a molding agent has extremely poor molding properties, the molding cavity cannot be filled, and the molding unit weight stability cannot be guaranteed. A molding agent is added to the AgMe composite powder, wet granulation is performed, and then drying is performed; wherein, the molding agent is required to leave no other substances, such as other metal elements, when volatilizing; at the same time, it must have a certain viscosity and be formed into a solid form at room temperature, so that during subsequent drying, the molding agent can bond the fine powder together, which is convenient for subsequent molding. In some embodiments, the molding agent used is a mixed solution of one or more of PVA, PEG and PVP, and the weight percentage of the molding agent used in the AgMe composite powder containing additives is 0.2wt% to 20wt%; the mixing temperature is 70 to 100°C, and the drying temperature is 75 to 110°C, which can dry the water in the molding agent aqueous solution and leave the forming agent therein. Powders that are too coarse or too fine are not conducive to molding. After drying, they are sieved and granulated, and the mesh number of the sieve is 40 to 400 meshes.
[0052] In some embodiments, in step S3, the AgMe composite powder after granulation and drying is placed in a molding machine mold and subjected to a first pre-pressing to obtain AgMe (半)Semi-finished green body; then AgMe (半) Ag powder is added to the upper part of the semi-finished green body, and the second pressing is performed to obtain the lower layer of AgMe (半) , AgMe with Ag powder on the upper layer (半) / Ag composite body. Figure 1 AgW (半) / Ag composite skeleton microstructure metallographic diagram, Figure 1 In the example, W (tungsten) is used as the reinforcement phase Me, and the lower layer is AgW (半) Porous structure, the upper layer is pure Ag structure.
[0053] In the first pre-pressing, the weight G1 of the AgMe composite powder after granulation and drying is calculated as follows: G1 = [L 1 *L 2 *H*ρ*(1-C 2 )] / (1-C 1 -C 3 );
[0054] In the formula, C 1 is the silver content of AgMe composite powder, C 3 C is the glue content of AgMe composite powder; 2 For AgMe (终) Silver content in finished electrical contact composite materials, ρ is AgMe (终) Density of finished electrical contact composite material, L 1 , L 2 , H are AgMe (终) Length, width and thickness of finished electrical contact composite material; AgMe (半) The size of semi-finished green body and AgMe (终) The finished electrical contact composites have the same dimensions.
[0055] The unit weight of the Ag powder added in the second pressing is calculated based on the porosity of the AgMe semi-finished green body. Specifically, in the second pressing, the weight g1 of the Ag powder added is calculated as follows: g1 = (L 1 *L 2 *H*ρ)-G1*(1-C 3 );
[0056] Where, L 1 , L 2 , H are AgMe (终) The length, width and thickness of the finished electrical contact composite material; ρ is AgMe (终) Density of finished electrical contact composite material, G1 is the weight of AgMe composite powder after granulation and drying, C 3 is the glue content of AgMe composite powder;
[0057] After secondary molding and pressing, AgMe is obtained (半) / Ag composite green body, AgMe (半) In the Ag / Ag composite body, the Ag powder layer is used to infiltrate and fill the AgMe (半) Therefore, in the subsequent process, there is no need to place a silver infiltration sheet on the surface of the debonded skeleton before melt infiltration.
[0058] The pressure of the first pressing is mainly determined by the thickness of the finished product, because the thickness of the product remains unchanged after infiltration, and the thickness of the final finished product must be achieved after the first pressing. If it is greater than the thickness of the finished product, the pores of the blank are larger, and the pores inside the blank cannot be filled under the same silver weight. The pressure needs to be increased until the product reaches the thickness requirement of the finished product; if the blank thickness is thinner than the finished product thickness, the pores inside the blank become smaller. Under the same silver weight, silver will remain on the surface of the product, causing silver flow and unqualified products. The pressure needs to be reduced until the pressed AgMe (半) The semi-finished green body reaches the finished thickness.
[0059] The second pressing process is to press a certain weight of silver powder onto the blank, but the thickness of the AgMe (semi) blank pressed in the first pressing process cannot be changed, otherwise the internal porosity of the blank will be affected. Preferably, the pressure of the second pressing process is much smaller than the pressure of the first pressing process, so as to ensure that the first pressing process of AgMe (半) The density (or thickness, porosity) is not affected, and it is also beneficial for the subsequent infiltration to make the Ag layer fall off and directly melt into liquid silver, which can quickly penetrate into the AgMe layer under capillary action.
[0060] In some embodiments, the mold core in the first step of molding is in a "sawtooth" shape, so that the composite interface of the two layers of composite powder is in a "sawtooth" shape. When the powder is added again for pressing, the powder will be filled into the "sawtooth", effectively increasing the bonding strength between the layers of the molded blank, and the finished welding surface will show "sawtooth" after infiltration, which is conducive to distinguishing the contact welding surface and the working surface.
[0061] In step S4, the degumming process parameters take into account factors such as the colloid volatilization point and the AgMe blank sintering point. If the degumming temperature is too high, the colloid will carbonize to form graphite, causing pollution to the blank; if the temperature is too high, AgMe may sinter, the internal pores will disappear, and the capillary action cannot be achieved, and thus the infiltration cannot be achieved. If the degumming time is too short, the molding agent cannot be completely removed, and the product is prone to cracking during high-temperature infiltration. If the degumming time is too long, the efficiency is reduced. In some embodiments, the degumming temperature is 300°C to 650°C, and the degumming time is 0.5 hours to 10 hours. Considering the oxidation of Me and additives in the blank, the oxidizing atmosphere will cause some internal components to oxidize, causing deterioration. The degumming atmosphere is H 2, any one of hydrogen and nitrogen mixed gas and vacuum.
[0062] In step S5, the infiltration process is capillary action, which is a slow adsorption and filling process, and it takes a certain amount of time to fill the entire blank pores. According to the infiltration principle, the finer the micropores, the stronger the adsorption force. The infiltration temperature needs to be higher than the melting point of silver (965 degrees), otherwise the silver cannot melt and cannot form a liquid phase. The higher the infiltration temperature, the lower the viscosity of pure silver, the more favorable the "capillary action", and the better the infiltration effect, but the temperature is too high and the energy consumption is high. In some embodiments, no infiltration sheet is added, and the AgMe (半) The Ag / Ag composite skeleton is placed in a continuous furnace and infiltrated under a protective atmosphere; wherein the infiltration temperature is 980°C to 1200°C, the infiltration time is 2 hours to 7 hours, and the infiltration atmosphere is H 2 Or hydrogen and nitrogen mixed gas.
[0063] In the above embodiment of the present invention, a large number of tiny pores exist between the powders during molding. After the green body is degummed, the internal tiny pores further increase. These tiny pores will produce capillary action under high temperature and liquid silver. Under the capillary action, the liquid silver will slowly absorb into the interior of the green body and fill into each tiny pore.
[0064] The method of preparing AgW, AgWC, or AgWC-W by the melt infiltration method or powder metallurgy powder pressing and sintering method of the present invention is significantly different. Specifically, the present invention first prepares WC or W powder and other reinforcing phase Me powder, Ag powder and additive X to prepare composite powder, and then mixes and granulates the powder, and then presses it into AgMe (半) / Ag composite green body, debonding, melt infiltration; during molding, first add the granulated powder into the mold cavity for the first pre-pressing, then add silver powder and perform the second pressing to form the lower layer of AgMe (半) Composite material, composite body with silver powder on the upper layer. During degumming, the lower layer of the composite body is AgMe (半) The molding agent in the material is decomposed and gasified by heat to form the lower layer of AgMe with a certain porosity. (半) The upper layer is a composite skeleton of pure silver powder. During infiltration, the composite skeleton is subjected to high temperature, the silver powder layer begins to melt, and enters the AgMe (半) Layer, filled with AgMe (半) The pores of the layer, if AgMe (半) / Ag The Ag layer of the blank is placed on top, and then filling is carried out from top to bottom. (半) The Ag layer of the Ag body is placed at the bottom, and then filled from bottom to top to form AgMe (终) Electrical contact composites.
[0065] The method in the above embodiment of the present invention avoids the misalignment of the infiltration sheet and the frame, which is conducive to improving the consistency of the product infiltration, thereby improving the material density and yield rate of the product, improving the contact resistance stability of the working surface of the electrical contact, extending the service life of electrical appliances such as circuit breakers, and reducing the temperature rise of the product. In addition, the method in the embodiment of the present invention omits the panning process of the infiltration sheet, the method is simple and easy to implement, suitable for large-scale production, high yield rate, stable performance, and can save processing costs.
[0066] Another embodiment of the present invention provides a melt-infiltration silver-based electrical contact material, which is prepared by the above-mentioned preparation method of the melt-infiltration silver-based electrical contact material. The material has the same technical effect as in the above-mentioned method embodiment, and will not be described in detail here.
[0067] The scheme of the present application will be explained below in conjunction with specific embodiments and comparative examples. It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained through commercial channels.
[0068] Example 1
[0069] The infiltration silver-based electrical contact material provided in this embodiment is an AgW50 electrical contact material (size: 0.7 cm wide, 1 cm long, and 0.2 cm thick), and its preparation method includes the following steps:
[0070] Step 1: 35wt% of Ag powder with a particle size of 100nm, 64wt% of W powder with a particle size of 20um, and 1wt% of Ni powder are premixed in a powder mixer, and then wet-mixed in a ball mill for high-energy mixing to obtain AgW composite powder containing Ni additive. The mixing time is 0.5 hours, and the ball-to-material ratio (i.e., the weight ratio of balls to powder) is 10.
[0071] In the second step, 10 wt % of PVA molding agent was added to the AgW composite powder for granulation at a mixing temperature of 90° C., followed by drying at 100° C. and passing through a 400-mesh sieve.
[0072] Step 3: First, place 1.465g of AgW powder after mixing, granulating and drying in the molding mold, and use the "sawtooth" shaped molding upper mold core to perform the first pre-pressing with a thickness of 0.2cm. Then, continue to add 0.439g of Ag powder on the upper part of the AgW semi-finished green body in the mold cavity, and perform the second pressing with a pressure much smaller than the first pressing force to obtain an AgW / Ag composite body with the lower layer being AgW composite powder and the upper layer being Ag powder.
[0073] Note: According to G1=[L1 *L 2 *H*ρ 2 *(1-C 2 )] / (1-C 1 -C 3 ) and g1=(L1*L2*H*ρ 2 )-G1 formula, and the finished product AgW50 density is: 13.6g / cm 3 , finished product size is width L 1 :0.7cm, length L 2 : 1cm; Thickness H: 0.2cm, Silver content of finished product C 2 =50wt%, AgW powder silver content C 1 35wt% and the rubber content C 3 is 10wt%; it can be calculated as follows:
[0074] G1=0.7×1×0.2×13.6×(1-50%)÷(1-35%-10%)=1.731g;
[0075] g1=0.7×1×0.2×13.6-1.731×(1-10%)=0.346g.
[0076] Step 4: Degumming the formed AgW / Ag composite body to obtain an AgW / Ag composite skeleton with a porous AgW layer at the bottom and a pure silver powder layer at the top; wherein the degumming temperature is 500°C, the degumming time is 8 hours, and the degumming atmosphere is H 2 .
[0077] Step 5: Place the debonded AgW / Ag composite skeleton in a continuous furnace and perform infiltration under a protective atmosphere to obtain an AgW electrical contact composite material. Preferably, the infiltration temperature is 980°C; the holding time is 3.5 hours, and the infiltration atmosphere is H 2 .
[0078] This embodiment finally obtains AgW50 electrical contact material with good performance, wherein the silver point hardness HV 5 is 161, the material structure is uniformly dispersed, such as Figure 2 The AgW50 microstructure after infiltration shown in the figure has a dispersed distribution of the reinforcing phase W and a uniform structure. Compared with the traditional infiltration process, the electrical life of the electrical contact is increased by 15%, the temperature rise is reduced by 10%, the yield rate is increased by 16%, and the production cost is reduced by 20%.
[0079] Example 2
[0080] The infiltration silver-based electrical contact material provided in this embodiment is an AgWC85 electrical contact material (size: 1.5 cm wide, 1 cm long, and 0.25 cm thick), and its preparation method includes the following steps:
[0081] Step 1: 8wt% of Ag powder with a particle size of 50μm, 92wt% of WC powder with a particle size of 50nm, and 3wt% of Co powder are placed in a ball mill with wet high-energy spheroidal graphite, and passed through a 400-mesh sieve to obtain AgWC composite powder containing additive Co. The ball milling time is 24 hours, and the ball-to-material ratio (i.e., the weight ratio of balls and powder) is 1.
[0082] In the second step, 20 wt % of PEG forming agent was added to the AgWC composite powder for granulation at a mixing temperature of 100° C., followed by drying at 110° C. and passing through a 200-mesh sieve.
[0083] The third step: first, place 6.455g of AgWC powder after mixing, granulation and drying in the mold of the molding machine, and use a "sawtooth" shaped molding upper mold core to perform the first pre-pressing with a thickness of 0.25cm. Then, continue to add 0.304g of Ag powder to the upper part of the AgWC semi-finished green body in the mold cavity, and perform the second pressing with a pressure much smaller than the first pressing force to obtain an AgWC / Ag composite body with an AgWC composite powder on the lower layer and Ag powder on the upper layer.
[0084] Note: According to G1=[L 1 *L 2 *H*ρ 2 *(1-C 2 )] / (1-C 1 -C 3 ) and g1=(L 1 *L 2 *H*ρ 2 )-G1*(1-C 3 ) formula, and the finished product AgWC85 density is: 14.56g / cm 3 , finished product size is width L 1 :1.5cm, length L 2 : 1cm; thickness H: 0.25cm, finished product silver content C2 = 15wt%, AgW powder silver content C 1 8wt% and the rubber content C 3 is 20wt%; it can be calculated as follows:
[0085] G1=1.5×1×0.25×14.56×(1-15%)÷(1-8%-20%)=6.445
[0086] g; g1=1.5×1×0.25×14.56-6.445×(1-20%)=0.304g.
[0087] Step 4: Degumming the formed AgWC / Ag composite body to obtain an AgWC / Ag composite skeleton with a lower layer of a porous AgWC layer and an upper layer of a pure silver powder layer; wherein the degumming temperature is 300° C., the degumming time is 10 hours, and vacuum degumming is adopted.
[0088] Step 5: Place the debonded AgWC / Ag composite skeleton in a continuous furnace and perform infiltration under a protective atmosphere to obtain an AgWC electrical contact composite material. Preferably, the infiltration temperature is 1200°C; the holding time is 2 hours, and the infiltration atmosphere is a nitrogen-hydrogen mixed gas.
[0089] This embodiment finally obtains AgWC85 electrical contact material with better performance, wherein the silver point hardness HV5 is 210, and the material structure is evenly dispersed. Compared with the traditional sheet infiltration process, the electrical life of the electrical contact is increased by 10%, the temperature rise is reduced by 25%, the yield rate is increased by 22%, and the production cost is reduced by 25%.
[0090] Example 3
[0091] The infiltration silver-based electrical contact material provided in this embodiment is an Ag65-W30-WC5 electrical contact material (size: 0.8 cm wide, 0.8 cm long, and 0.2 cm thick), and its preparation method includes the following steps:
[0092] Step 1: 50wt% of Ag powder with a particle size of 10μm, 42.8wt% of WC powder with a particle size of 3μm, 7.2wt% of WC powder with a particle size of 1μm, and 0.5wt% of ZnO powder are placed in a powder mixer for dry mixing to obtain Ag-W-WC composite powder containing additive ZnO. The ball milling time is 10 hours, and the ball-to-material ratio (i.e., the weight ratio of balls and powder) is 5.
[0093] In the second step, 0.2wt% of PVP molding agent was added to the AgWC composite powder for granulation. The mixing temperature was 70°C, followed by drying at 75°C and passing through a 40-mesh sieve.
[0094] The third step: first, place 6.455g of AgWC powder after mixing, granulation and drying in the mold of the molding machine, and use the "sawtooth" shaped molding upper mold core to perform the first pre-pressing with a thickness of 0.2cm. Then, continue to add 0.304g of Ag powder on the upper part of the AgWC semi-finished green body in the mold cavity, and perform the second pressing with a pressure much smaller than the first pressing force to obtain an AgWC / Ag composite body with the lower layer being AgWC composite powder and the upper layer being Ag powder.
[0095] Note: According to G1=[L 1 *L 2 *H*ρ 2 *(1-C 2 )] / (1-C1 -C 3 ) and g1=(L 1 *L 2 *H*ρ 2 )-G1*(1-C 3 ) formula, and the finished product Ag65-W-WC density is: 12.4g / cm 3 , finished product size is width L 1 :0.8cm, length L 2 : 0.8cm; Thickness H: 0.2cm, Silver content of finished product C 2 =65wt%, AgW powder silver content C 1 50wt% and the rubber content C 3 is 0.2wt%; it can be calculated as follows:
[0096] G1=0.8×0.8×0.2×12.4×(1-65%)÷(1-50%-0.2%)=1.115g;
[0097] g1=0.8×0.8×0.2×12.4-1.115×(1-0.2%)=0.474g.
[0098] Step 4: Degumming the formed Ag-W-WC / Ag composite body to obtain an Ag-W-WC / Ag composite skeleton with a lower layer of a porous AgW-WC layer and an upper layer of a pure silver powder layer; wherein the degumming temperature is 650°C, the degumming time is 0.5 hour, and the degumming atmosphere is a nitrogen-hydrogen mixed gas.
[0099] Step 5: Place the debonded Ag-W-WC / Ag composite skeleton in a continuous furnace and perform infiltration under a protective atmosphere to obtain an Ag-W-WC electrical contact composite material. Preferably, the infiltration temperature is 1100°C; the holding time is 7 hours, and the infiltration atmosphere is a nitrogen-hydrogen mixed gas.
[0100] This embodiment finally obtains Ag65-W30-WC5 electrical contact material with good performance, wherein the silver point hardness HV5 is 130, and the material structure is evenly dispersed. Compared with the traditional sheet infiltration process, the electrical life of the electrical contact is increased by 5%, the temperature rise is reduced by 15%, the yield rate is increased by 12%, and the production cost is reduced by 30%.
[0101] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essence of the present invention. The above preferred features can be used in any combination without conflicting with each other.
Claims
1. A method for preparing a melt-infiltration silver-based electrical contact material, characterized in that: include: Mixing and grinding Ag powder, reinforcing phase Me powder and additive powder to obtain AgMe composite powder containing additive; The AgMe composite powder containing additives is mixed with glue and granulated; The granulated AgMe composite powder is double-layer pressed, where the lower layer is AgMe (半) layer, the upper structure is Ag layer, and AgMe (半) / Ag composite body; The AgMe (半) The Ag / Ag composite body is debonded to obtain AgMe (半) / Ag composite framework; The AgMe (半) / Ag composite framework is melt-infiltrated at high temperature to obtain AgMe (终) The electric contact composite material is a melt-infiltration type silver-based electric contact material.
2. The method for preparing the infiltration silver-based electrical contact material according to claim 1, characterized in that: The Ag powder, the reinforcing phase Me powder and the additive powder are mixed and ground, wherein: The content of the reinforcing phase Me powder is not less than 35wt% and not more than 85wt% of the total weight of the finished product after infiltration, the content of the additive powder is not more than 3wt% of the total weight of the mixed powder, and the balance is Ag powder; The additive powder is an element or compound that can be wetted with the reinforcing phase Me powder and cannot be infinitely mutually soluble with Ag; The particle size of the Ag powder is 100nm-50μm; the particle size of the reinforcing phase Me powder is 50nm-20μm.
3. The method for preparing the infiltration silver-based electrical contact material according to claim 1, characterized in that: The Ag powder, the reinforcing phase Me powder and the additive powder are mixed and ground, wherein: The mixing and grinding is carried out by any one of dry mixing and grinding, wet mixing and grinding, and dry mixing and grinding followed by wet mixing. The mixing and grinding time is 0.5 to 24 hours; and the ball-to-material ratio is 1 to 10.
4. The method for preparing the infiltration silver-based electrical contact material according to claim 1, characterized in that: The AgMe composite powder containing additives is subjected to rubber mixing and granulation, comprising: Adding a molding agent to the AgMe composite powder, granulating, and then drying and sieving; wherein the molding agent used is a mixed solution of one or more of PVA, PEG and PVP, and the weight percentage of the molding agent used in the AgMe composite powder containing the additive is 0.2wt% to 20wt%; The mixing temperature of the glue is 70-100°C, the drying temperature is 75-110°C, and after drying, it is sieved with a mesh number of 40-400 meshes.
5. The method for preparing the infiltration silver-based electrical contact material according to claim 1, characterized in that: The AgMe after granulation and drying (半) The powder is pressed into shape, including: First, the AgMe composite powder after granulation and drying is placed in the molding machine mold for the first pre-pressing to obtain AgMe (半) Semi-finished green products; Then in the mold cavity, AgMe (半) Ag powder is added to the upper part of the semi-finished green body, and the second pressing is performed to obtain the lower layer of AgMe (半) , AgMe with Ag powder on the upper layer (半) / Ag composite body.
6. The method for preparing the infiltration silver-based electrical contact material according to claim 5, characterized in that: In the first pre-pressing, the weight G1 of the AgMe composite powder after granulation and drying is calculated as follows: G1 = [L1*L2*H*ρ*(1-C2)] / (1-C1-C3); Where, C1 is the silver content of AgMe composite powder, C3 is the glue content of AgMe composite powder; C2 is AgMe (终) Silver content in finished electrical contact composite materials, ρ is AgMe (终) Density of finished electrical contact composite materials, L1, L2, H are AgMe (终) The length, width and thickness of the finished electrical contact composite material; The AgMe (半) The size of semi-finished green body and AgMe (终) The finished electrical contact composites have the same dimensions.
7. The method for preparing the infiltration silver-based electrical contact material according to claim 5, characterized in that: In the second pressing, the weight g1 of the added Ag powder is calculated as follows: g1 = (L1*L2*H*ρ)-G1*(1-C3); Wherein, L1, L2, H are AgMe (终) The length, width and thickness of the finished electrical contact composite material; ρ is AgMe (终) The finished product density of the electrical contact composite material, G1 is the weight of the AgMe composite powder after granulation and drying, and C3 is the glue content of the AgMe composite powder; The AgMe (半) In the Ag / Ag composite body, the Ag powder layer is used to infiltrate and fill the AgMe (半) Layer skeleton pore material.
8. The method for preparing the infiltration silver-based electrical contact material according to claim 1, characterized in that: The AgMe (半) The Ag / Ag composite body is debonded, wherein: the debonding temperature is 300°C to 650°C, the debonding time is 0.5 hour to 10 hours, and the debonding atmosphere is any one of H2, hydrogen-nitrogen mixed gas and vacuum.
9. The method for preparing the infiltration silver-based electrical contact material according to claim 1, characterized in that: The AgMe (半) / Ag composite skeleton is subjected to high temperature infiltration, including: debonding AgMe (半) The / Ag composite framework is placed in a continuous furnace and infiltrated under a protective atmosphere; The infiltration temperature is 980°C to 1200°C, the infiltration time is 2 hours to 7 hours, and the infiltration atmosphere is H2 or a hydrogen-nitrogen mixed gas.
10. A melt-infiltrated silver-based electrical contact material, characterized in that: The silver-based electrical contact material is prepared by the preparation method of the infiltration type according to any one of claims 1 to 9.
Citation Information
Patent Citations
Silver-tungsten electric contact material and preparing method thereof
CN108441668A